دراسة تحليلية لمؤشرات استدامة الاقتصاد الجزائري - شرفاوي, عائشة (جامعة الوادي - University of Eloued, 2023)
تهدف الدراسة لتحليل مدى استدامة الاقتصاد الجزائري، بالتطرق إلى أهم المؤشرات الموضوعة من طرف الهيئات الدولية في ذات الشأن، ما يسمح بتحديد أهم العوامل الضرورية التي يجب الاهتمام بها حاليا ومستقبلا لتحقيق التنمية المستدامة المرجوة في جميع القطاعات الاقتصادية، توصلت الدراسة إلى أن الاقتصاد الجزائري يسجل مستويات متدنية في مؤشرات الاستدامة الاقتصادية، بالمقارنة مع المعايير المعتمدة دوليا فتعزيز استدامة الاقتصاد الجزائري مرهون بالدرجة الأولى بالتطبيق الفعلي للسياسيات الموضوعة من طرف الدولة لتحسين مؤشرات استدامة لتصبح مقبولة نسبيا بالمقارنة بالدول الرائدة في هذا المجال . The study aims to analyze and study the extent of the sustainability of the Algerian economy, by referring to the most important indicators set by international bodies in this regard. The study concluded that the Algerian economy records low levels in indicators of economic, social and environmental sustainability compared to internationally approved standards. Achieving the sustainability of the Algerian economy depends primarily on With the actual application of the policies set by the Algerian state, achieving the required balance between the economic, social and environmental dimensions calls for more research and work to raise the indicators of sustainability
An analytical study of the indicators of the sustainability of the Algerian economy
مقال
Keywords: الاقتصاد المستدام ; مؤشرات الاستدامة ; الاقتصاد الجزائري; Sustainable economy, indicators of sustainability, the Algerian economy